TRABALHO, GESTÃO E CAPACITAÇÃO NA PANDEMIA DA COVID-19: PERCEPÇÃO DE PROFISSIONAIS DA ATENÇÃO PRIMÁRIA À SAÚDE - Maristela Rodrigues Marinho (2021)
Introduction: Primary Health Care (PHC) has a fundamental role in the response to outbreaks and epidemics, as it is the system's gateway, constituting an important pillar in the face of emergency situations. Objective: To identify and analyze the perception of health professionals about the work and management of PHC during the Coronavirus Disease 2019 pandemic (COVID-19). Methodology: Study of quantitative approach, analytical cross-sectional, Survey type, carried out on a random sample of 259 professionals working in management and/or care, within the scope of PHC, in the states of Mato Grosso do Sul (MS) and São Paulo (SP), from June to October 2020. A semi-structured virtual questionnaire was applied to obtain sociodemographic data and with questions about the perceptions of professionals about work and management in the pandemic. Descriptive analysis of sociodemographic data and Fisher's exact test were performed to test associations. Result: The majority were female (85.3%), nursing professionals (40.6%), average age of 39.1 years, college level (43.2%), working in direct care (69.5 %). There was a significant association between employment and professional category (p=0.0280); early immunization against influenza and status of action (p=0.0306); access to tests for virus detection and performance status (p=0.0012); type of protection mask and function performed (p=0.0195); type of mask provided and professional category (p=0.0005). Most professionals did not participate in training: ACS and ACE (76.6%), nursing assistants/technicians (45.2%) and higher education (26.1%). When offered, the courses were held at the workplace, with a workload between 15 and 30 hours, using the distance learning methodology. As for the logistics related to the flow of care and transport, there was a difference between the perception of professionals working in care and management (p=0.05), with a more positive view of management professionals. Conclusion: The results demonstrate the difficulties faced by PHC professionals, such as: lack of training, lack of human resources, deficiency of Personal Protective Equipment, physical structure of the units and inadequate logistics to meet the demand. Therefore, public and management policies need to be implemented, valuing PHC and its professionals, ensuring training, adequate working conditions and sufficient investments to face the pandemic Keywords: Primary Health Care. COVID-19. Coronavirus. Worker's health. Health education. Health surveillanc. Health management.